Analysis of the Utilization of the E-Sensi Attendance Application and the Work Environment in Building Employee Work Discipline at the NTB Provincial Cultural Park - Adiwidnyana, Ida Bagus; Sudarma, I Made; Chandra, Edy (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study examines the utilization of the E-Sensi attendance application and the role of the work environment in building employee work discipline at the NTB Provincial Cultural Park. Using a qualitative case study approach, data were collected through in-depth interviews with 13 employees, observation, and documentation, and analyzed using thematic analysis. The findings indicate that GPS- and photo-based E-Sensi effectively reduces attendance manipulation, although technical issues such as system errors and internet quota limitations persist. A supportive work environment strengthens discipline through positive social norms and interpersonal relationships. Employee discipline is shaped by the interaction of technological control, work environment conditions, and economic incentives from TPP. The study concludes that an integrated approach combining technology optimization, work environment improvement, and consistent sanction enforcement is more effective than partial interventions.